2020
DOI: 10.1016/j.cca.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

ACE deletion allele is associated with susceptibility to SARS-CoV-2 infection and mortality rate: An epidemiological study in the Asian population

Abstract: Highlights Differential distribution of ACE I/D polymorphism observed in Asian countries. Allele D of ACE I/D polymorphism was associated with susceptibility to SARS-CoV-2 infection. The minor allele of ACE I/D was linked with COVID-19 mortality in the Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 24 publications
4
76
1
2
Order By: Relevance
“…The European population has a lower ACE1 II genotype frequency and a higher prevalence of infected patients and mortality due to COVID-19 than the Asian population [ 78 ]. These data are consistent with an epidemiological study that reported a significant positive correlation of the D allele with SARS-CoV-2 infection prevalence and mortality rate in Asian population [ 79 ]. The DD genotype was also increased in acute respiratory distress syndrome [ 80 ].…”
Section: Genetic Polymorphismsupporting
confidence: 92%
“…The European population has a lower ACE1 II genotype frequency and a higher prevalence of infected patients and mortality due to COVID-19 than the Asian population [ 78 ]. These data are consistent with an epidemiological study that reported a significant positive correlation of the D allele with SARS-CoV-2 infection prevalence and mortality rate in Asian population [ 79 ]. The DD genotype was also increased in acute respiratory distress syndrome [ 80 ].…”
Section: Genetic Polymorphismsupporting
confidence: 92%
“…ACE1-DD carriers have higher blood levels of ACE, approximately twice when compared to ACE1-II individuals, and have been associated with hypertension, ARDS, and in-hospital mortality [ 146 – 148 ]. Therefore, the deletion allele is associated with COVID-19 progression [ 89 ] and SARS-CoV-2 infection rate and mortality [ 147 ], while the ACE1-II genotype negatively correlates with infection rate and mortality [ 149 ]. However, a meta-analysis (48,758 healthy subjects from 30 different countries) significantly associated ACE1-I/D allele frequency ratio with the increase in the recovery rate, but not with mortality [ 150 ].…”
Section: Ace1/ace2 Gene Polymorphismsmentioning
confidence: 99%
“…According to the available data, the frequency of D allele is positively correlated with the number of SARS-CoV-2 infection cases in Asians and African Americans. 32 , 54 Owing to the combined effect of D allele and SARS-CoV-2 infection, the high ACE levels and decreased ACE2 levels lead to a high amount of Ang II in plasma and tissues and eventually result in severe lung injury and even death.…”
Section: Role Of Ras In Ali Caused By Coronavirus Infectionsmentioning
confidence: 99%